NON-PHARMACOLOGICAL APPROACHES TO PAIN MANAGEMENT IN ENDOMETRIOSIS: A REVIEW OF CURRENT EVIDENCE - Eliza Kawalska; Kacper Szymon Zielonka; Joanna Jasińska; Bartosz Dądela; Marcin Markowski; Natalia Śliwa; Sara Langner; Szymon Gnitecki; Szymon Janczura; Maciej Borowski (International Journal of Innovative Technologies in Social Science, 2025)
Endometriosis is a chronic inflammatory disorder affecting approximately 10% of women of reproductive age, typically associated with intense pelvic pain, dyspareunia, and menstrual irregularities. While pharmacological and surgical therapies remain the cornerstone of treatment, there is growing interest in non-pharmacological strategies for symptom management, particularly among individuals who cannot take medications or prefer to limit their use. This review aims to evaluate current scientific research on the effectiveness of non-pharmacological methods for managing endometriosis-related pain. The analysis includes approaches such as acupuncture, physiotherapy, physical activity, yoga, dietary adjustments, nutritional supplementation, and psychological interventions. Evidence from multiple studies suggests that these strategies can significantly alleviate pain, enhance quality of life, and support psychological well-being. The review emphasizes the need for additional well-designed clinical trials to confirm their effectiveness and better integrate these methods into routine clinical practice.